Impact of membrane pore structure on protein detection sensitivity of affi nity-based immunoassay - Ahmad, A.L.; Ideris, N.; Ooi, B.S.; Low, S.C.; Ismail, A. (De Gruyter Open, 2016)
Understanding a membrane’s morphology is important for controlling its fi nal performance during protein immobilization. Porous, symmetric membranes were prepared from a polyvinylidene fl uoride/N-methyl-2-pyrrolidinone solution by phase inversion process, to obtain membrane with various microsized pores. The concentration and surface area of aprotein dotted on the membrane surface were measured by staining with Ponceau S dye. The dotted protein was further scanned and analysed to perform quantitative measurements for relative comparison. The intensity of the red protein spot and its surface area varied depending on the membrane pore size, demonstrating the dependence of protein immobilization on this factor. The membrane with the smallest pore size (M3) showed the highest protein spot intensity and surface area when examined at different protein concentrations. An increase in the applied protein volume showed a linearity proportional trend to the total surface area, and an uneven round dot shape was observed at a large applied volume of protein solution.